A Complete Arduino-Based Mathematical Pendulum Experiment Tool with Real-Time Data Acquisition Using an Excel Spreadsheet - Fauzi, Ahmad; Marwoto, Putut; Nugroho, Sunyoto Eko (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
It is very important for students to understand the concept of simple harmonic motion, such as a mathematical pendulum. Students need an experiment tool on mathematical pendulums that is capable of providing measurement results of various physical quantities of mathematical pendulums accurately and precisely. This research aims to (1) describe the specifications of an Arduino-based mathematical pendulum experiment tool, (2) describe the results of measurements of acceleration due to gravity, and (3) describe the effect of changes in deviation on the period at small angles. This research used the experiment method. The research results showed that (1) the Arduino-based mathematical pendulum experiment device is equipped with an HC-SR04 ultrasonic sensor to measure the length of the string and an FC-51 infrared sensor to measure the period with a precision of 94.9% and accuracy of 99%, (2) the average result of acceleration due to gravity measurements at various string length was (9.72 ± 0.19) m/s2,and (3) the mathematical pendulum period between angles of 1-13 degrees did not show a significant difference, showing that at small angles, the oscillation period is not affected by deviation.